Vaccine nationalism: a predicament in ending the COVID-19 pandemic - Lagman, James Darwin N (J Public Health (Oxf), 2021)
In a recent correspondence, vaccine hesitancy and its pressing issue in possible delaying of being triumphant in the pandemic was discussed. This paper highlights vaccine nationalism as a predicament that would not just delay but worsen the present situation of the pandemic. This study suggests a global response among countries that people must see the world as a global village and as one community it must save collectively.